PATHOLOGICAL ASPECTS OF SKELETAL MUSCLE IN EXPERIMENTAL Trypanosoma cruzi INFECTION - A Lugo de Yarbuh; C Colasante (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
Clinical observations were made of mice in the acute stage of infection produced by three Trypanosoma cruzi strains. Mice infected with Dm74 suffered complete paralysis of the rear limbs followed by death, while still in the acute stage of Chagas' disease. Hystological analysis of skeletal muscle showed intense inflammatory infiltrates of mononuclear and polymorphonuclear leukocytes, fibroblasts, free red blood cells and IgG deposits in the interstilium of Gastrocnemius (G). Local miofibrillic disintegration and changes in microvessels, nerve fibers and the neuromuscular junction of G were also observed. These results indicate that the acute infection with T. cruzi may cause progressive damage in parasite infected muscle fiber and lead to loss of mobility.